PENALARAN TA‘LILIYAH QIYASIYAH - Zaki Satria (SYARIAH: Journal of Islamic Law, 2021)
In the preparation of reasoning rules, the dominie who is considered the most  meritorious is Imam al-Syafi'i. the results of Imam al-Syafi'i's thought are considered the most comprehensive and systematic, therefore to some extent considered as corrections and completions of the rules compiled and used by Imam Abu Hanifah and Imam Malik. In recent times, these rules have been supplemented and refined, especially by the scholars of the Al-Ghazali generation (fifth century hijriah) and after that in the generation of Fakhr al-Din al-Razi (sixth century Hijriah), so that they are considered standard and perfect. In this paper the author will try to explain the reasoning of the qiyasiyah ta'liliyah along with an example, namely qiyas between licking dogs on clothes, human limbs and all objects to licking dogs on vessels, because 'illat is that the dog's saliva is heavy unclean and is required to wash. seven times with water and one of them with earth or soap, which is a method of determining Islamic law.